Maternal Education Level Predicts Cognitive, Language, and Motor Outcome in Preterm Infants in the Second Year of Life - Patra, Kousiki; Greene, Michelle M.; Patel, Aloka L.; Meier, Paula (American Journal of Perinatology, 2016)
Objective To evaluate the relative impact of maternal education level (MEL) on cognitive, language, and motor outcomes at 20 months' corrected age (CA) in preterm infants.Study Design A total of 177 preterm infants born between 2008 and 2010 were tested at 20 months' CA using the Bayley Scales of Infant and Toddler Development-III. Multiple regression analyses were done to determine the relative impact of MEL on cognitive, language, and motor scores.Results Infants born to mothers with high school MEL were 3.74 times more likely to have a subnormal motor index, while those born to mothers with some college and graduate school MEL had reduced odds (0.36 and 0.12, respectively) of having subnormal language index at 20 months. In linear regression, MEL was the strongest predictor of cognitive, language, and motor scores, and graduate school MEL was associated with increases in cognitive, motor, and language scores of 8.49, 8.23, and 15.74 points, respectively.Conclusions MEL is the most significant predictor of cognitive, language, and motor outcome at 20 months' CA in preterm infants. Further research is needed to evaluate if targeted interventions that focus on early childhood learning and parenting practices can ameliorate the impact of low MEL.
Keywords: maternal education; neurodevelopmental outcomes; prematurity; motor outcome